2002
DOI: 10.1080/09553000210134791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dose and dose-distribution in damage to the kidney following abdominal radiotherapy

Abstract: Sophisticated imaging techniques allow the identification of radiation effects in partial volumes of the kidneys. A dose-response relationship in relation to the volume of kidney irradiated can thus be established for scintigraphic changes. As in a number of other organs, such changes do not relate directly to loss of renal function due to the reserve capacity of unirradiated kidney tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…A pronounced variation in irradiated volume is inherent in the present study, as indicated by the range of kidney volumes [14] and liver volumes (Köst et al, in preparation) exposed. The volumes of intestine irradiated in the individual patients, however, remain unclear, although most treatments were 3-D-planned and dose histograms are available.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A pronounced variation in irradiated volume is inherent in the present study, as indicated by the range of kidney volumes [14] and liver volumes (Köst et al, in preparation) exposed. The volumes of intestine irradiated in the individual patients, however, remain unclear, although most treatments were 3-D-planned and dose histograms are available.…”
Section: Discussionmentioning
confidence: 93%
“…The diagnoses were lymphogranulomatosis (n = 22), non-Hodgkin's lymphoma (NHL, n = 13), gastric NHL (n = 4), seminoma (n = 45), carcinoma of the kidney (right: n = 4, left: n = 2), and rhabdomyosarcoma (n = 1). The patients have been characterized in detail elsewhere [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interstitial damage due to ischemia, toxic enzymes and drugs diminishes tubular uptake of DMSA and produces abnormalities seen on scintigraphy during or after renal parenchymal pathologies [5,26]. Experimental studies in animals demonstrated that drug-induced nephrotoxicity or radiation-induced changes reduce tubular uptake of 99m Tc DMSA in kidneys even if a minor fraction of the organ is involved [1,16,21]. Therefore, our model is suitable for the evaluation of relative changes in renal function (ipsilateral vs. contralateral) and of the efficacy of amifostine.…”
Section: Discussionmentioning
confidence: 99%
“…Since the complication rate curve in normal tissue is very steep for the kidneys, even slightly greater doses of 25 to 30 Gy raise that rate to !50%, and doses above 40 Gy to the entire organ cause nephropathy in most patients [26Á28]. Scintigraphic changes without clinical symptoms can be observed at doses of B10 Gy to the whole kidney [29]. Follow-up periods in these studies have not exceeded 8 years; therefore, caution is recommended for calculating doses for patients with longer expected survival times.…”
Section: Discussionmentioning
confidence: 99%